Ichthyofaunal Diversity and Physico-Chemical Factors of Melamchi River, Sindhupalchok, Nepal - Mishra, Abha R.; Baniya, Chitra Bahadur (Journal of Institute of Science and Technology, 2016)
The fish community and physico-chemical properties at five sites of Melamchi River were studied monthly from January 2011 to December 2013. Melamchi River is one of tributaries larger Indrawati River basin, originates from the high snowy Jugal Mountain (5,875 m asl). Eleven fish species within two orders and five families were recorded. Cypriniformes was found to be the most dominant order with ten fish species. Schizothorax plagiostomus was the most common fish species followed by Neolissochilus hexagonolepis, and Psilorhynchus pseudecheneis. Shannon Wiener fish diversity index and species richness recorded were highest at site 2 and lowest at site 5, whereas, evenness index was highest at site 3. The cluster analysis revealed that similarity between fish species decreased as the distance between the sites increased. Fish species were found distributed among four groups with respect to the significant habitat characteristics in the redundancy analysis (RDA). River water was found well-oxygenated and alkaline at all sites. However, high level for turbidity (43.25/ NTU) was observed at site 5, which exceeded compliance levels of WHO indicating the influence of intensive agriculture and deforestation along river area. To improve fish diversity and water quality of this river proper monitoring and management are an urgent need. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, Page: 10-18